2019
DOI: 10.1017/bec.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Patient Engagement in Outpatient Cardiac Rehabilitation Programs

Abstract: The primary aim of this study was to test the causal structure of the model of therapeutic engagement (MTE) for the first time, to examine whether the model assists in understanding the process of patient engagement in cardiac rehabilitation (CR) programs. This study used a prospective design, following up patients from the Gold Coast University Hospital Cardiology ward who attended Robina Cardiac Rehabilitation Clinic. A structural equation model of the interactions among the proposed variables within the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Research have also examined patients’ beliefs and attitudes toward their experiences of pain and the various methods used for pain relief, all of which contribute to the intricacy of the patients’ role in pain management ( Doekhie et al., 2020 ; Forsberg et al., 2015 ; Kästner et al., 2021 ). Several studies have reported on patient engagement and noted that aspects of patients’ expectations and attitudes were found to influence their level of participation in pain management ( Blumenthal-Barby, 2017 ; Davis et al., 2007 ; Jahandideh et al., 2019 ). Many patients were found to be misinformed about the risks associated with medications, the importance of self-reporting pain, and the potential complications of intense or unresolved pain ( Bjørnnes et al., 2017 ; Cogan et al., 2014 ; Komann et al., 2021 ; Milosevic et al., 2021 ; Schwenkglenks et al., 2014 ; van Dijk et al., 2017 ; Vu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research have also examined patients’ beliefs and attitudes toward their experiences of pain and the various methods used for pain relief, all of which contribute to the intricacy of the patients’ role in pain management ( Doekhie et al., 2020 ; Forsberg et al., 2015 ; Kästner et al., 2021 ). Several studies have reported on patient engagement and noted that aspects of patients’ expectations and attitudes were found to influence their level of participation in pain management ( Blumenthal-Barby, 2017 ; Davis et al., 2007 ; Jahandideh et al., 2019 ). Many patients were found to be misinformed about the risks associated with medications, the importance of self-reporting pain, and the potential complications of intense or unresolved pain ( Bjørnnes et al., 2017 ; Cogan et al., 2014 ; Komann et al., 2021 ; Milosevic et al., 2021 ; Schwenkglenks et al., 2014 ; van Dijk et al., 2017 ; Vu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, this review showed that the literature (including several empirical studies) supported subsets of the proposed relationships within the MTE in the context of CR. Another study (Jahandideh et al, 2019) investigated how the factors proposed by the MTE contributed to engagement, and interacted, through analysis of 101 participants who remained to commence the program. A key finding was that almost all relationships among the proposed factors within the three stages of engagement were found to be significant and consistent in terms of effect sign and size, with the MTE.…”
Section: Introductionmentioning
confidence: 99%